2017
DOI: 10.32890/jict2017.16.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Online Consumers’ Perceptions of Posted Comments: An Analysis of Tripadvisor Reviews

Abstract: Ratings and comments play a dominant role in online reviews. The question, thus, arises as to whether or not there is any consistency in consumer perception of the reviews, and how future choices might be influenced. We analysed 2000 comments of 20 different hotels posted on TripAdvisor to determine if the comments posted by previous guests of a hotel influence the decisions of potential guests. Two hundred human raters were asked to consider 20 reviews and to rate a hotel based on the reviews. The Cohen Kappa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A recent survey of Bizrate Insights reward members found that approximately 98% of online shoppers research a vendor via online reviews before making a purchase decision (Kats, 2018). Since the reviews are expected to describe the actual experiences and opinions of users, they can provide a reliable source of reference, improving other customers' confidence, comfort, and the overall shopping experience (Foo et al, 2017;Gamzu…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey of Bizrate Insights reward members found that approximately 98% of online shoppers research a vendor via online reviews before making a purchase decision (Kats, 2018). Since the reviews are expected to describe the actual experiences and opinions of users, they can provide a reliable source of reference, improving other customers' confidence, comfort, and the overall shopping experience (Foo et al, 2017;Gamzu…”
Section: Introductionmentioning
confidence: 99%